Reciprocal relationship between unhealthy eating behaviours and depressive symptoms from childhood to adolescence: 10-year follow-up of the Child and Adolescent Behaviors in Long-Term Evolution study. Issue 9 (19th January 2016) - Wu, Wen-Chi; Luh, Dih-Lin; Lin, Ching-I; Chiang, Yi-Chen; Hung, Chao-Chia; Wang, Sabrina; Wu, Chi-Chen; Hurng, Baai-Shyun; Chang, Yi-Han; Yen, Lee-Lan; Chang, Hsing-Yi
Abstract: Objective: To investigate the reciprocal relationship between unhealthy eating behaviours and depressive symptoms from childhood to adolescence. Design: Unhealthy eating behaviours were measured by the frequencies of eating foods with excess salt, sugar or fat in the past week. Depressive symptoms in the past two weeks were measured using a seven-item scale. Hierarchical linear growth models were used to analyse longitudinal associations between unhealthy eating behaviours and depressive symptoms. Time-fixed variables (sex, parents' education level and household monthly income) and time-varying variables (parents' marital status, family activities, body weight, vegetable or fruit consumption, exercising and smoking) were controlled for. Setting: The Child and Adolescent Behaviors in Long-Term Evolution study, which commenced in 2001 and has annual follow-up. Subjects: Students ( n 2630) followed from 2nd grade (8 years old in 2002) to 11th grade. Results: The frequency of unhealthy eating behaviours in the previous year and the difference between the frequency in the previous and successive year were positively associated with the initiation and growth rate of depressive symptoms. Depressive symptoms in the previous year and the difference in depressive symptoms between the previous and successive year were positively associated with the initial state and growth rate of unhealthy eating behaviours. Conclusions: Our results suggest a reciprocal relationship between depressive symptoms and unhealthy eating behaviours. This relationship should be considered when developing programmes targeting depressive symptoms and unhealthy diet in children and adolescents.